2016
DOI: 10.1111/iju.13176
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of hematospermia in 189 Japanese men

Abstract: In patients with hematospermia without inflammation, infection or malignancy, it is important to provide information on the possibility that symptoms will resolve spontaneously and to implement measures to relieve their anxiety. Detection of seminal vesicle hemorrhage and a midline cyst of the prostate is important for prediction of the duration of hematospermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Furuya et al reported the natural history of hemospermia, and the rates of persistent hemospermia were 34.2% at 3 months, 23.3% at 6 months, 12.5% at 1 year and 7.6% at 2 years. 20 This natural course might be an interfering factor when analyzing the excellent remission rate after TUSV.…”
Section: Discussionmentioning
confidence: 99%
“…Furuya et al reported the natural history of hemospermia, and the rates of persistent hemospermia were 34.2% at 3 months, 23.3% at 6 months, 12.5% at 1 year and 7.6% at 2 years. 20 This natural course might be an interfering factor when analyzing the excellent remission rate after TUSV.…”
Section: Discussionmentioning
confidence: 99%
“…4 Since then there have been a number of significant papers published regarding the diagnosis and management of haematospermia. [5][6][7][8][9] In 2016, NICE also published guidelines on management of haematospermia. 10…”
Section: New Researchmentioning
confidence: 99%
“…Haematospermia resolves spontaneously in 88.9% of patients and its median duration is 1.5 months. 5 These patients require reassurance that their symptoms are not a sign of significant disease and that it should settle over time.…”
Section: Causesmentioning
confidence: 99%
“…Hematospermia usually self-resolves in many cases, stopping in occurrence over time, especially for patients below the age of 40. In a prospective study, Furuya et al concluded that in patients presenting with hematospermia without inflammation, infection, or malignancy, hematospermia resolved spontaneously in more than 88% of the patients with a mean disease duration of 1.5 months ( 114 ). Since hematospermia has a higher rate of persistence in patients with seminal vesical hemorrhage, midline cyst, seminal vesical dilation, and age older than 50, it is imperative that the underlying condition is properly diagnosed and treated to completely resolve hematospermia ( 114 ).…”
Section: Managementmentioning
confidence: 99%
“…Similarly, one of the most important aspects of managing hematospermia is patient reassurance. The physician must evaluate the patient, rule out life-threatening conditions such as cancer, and relieve the anxiety and stress meanwhile providing a proper follow-up and observation ( 114 ). Surgery should be performed and proper medication should be prescribed based on the pathophysiological nature of hematospermia.…”
Section: Managementmentioning
confidence: 99%